The poisonous wildlife Rimac Valley - Delgado Quiroz, Alvaro (1967)
In this paper, the study of the geographical environment of the Rimac valley is as representative of the Coast, considering environmental factors that influence on the ecology of the poisonous animals in their Tropical Medicine related to aspects. It collects, reviews and watch the wildlife of Lima, which is separated and the poisonous species taxonomically classified pointing at some of these pathogenicity for the first time in Lima.